World Economic Growth–Retrospect and Prospects - Adler, John H. (The Review of Economics and Statistics, 1956)
THE purpose of this paper is to review the trend of economic growth of the last ten years in the three most important parts of the free world: the countries of Western Europe and North America, of Latin America, and of Southeast Asia.' It focuses on the factors bearing most directly on long-run economic growth in these areas, including the volume of savings and investment, the role of international trade and capital movements, and the effects of price changes. An attempt is made to assess the prospects for growth in the years ahead and to draw some general lessons from the experience of the last decade. Since this paper is primarily concerned with discerning the long-run trend, year-to-year changes, and differences between individual economies, particular sectors of the economies could not be treated in more than a cursory way. For the same reason, it does not purport to present an economic survey of the three regions; nor does it constitute a world economic survey, since it does not cover the countries of the Far East, the Near East, the South Pacific, South Africa, or, excepting Malaya, any of the dependent territories. Developments in these areas differed so much from country to country, and from those of the areas discussed in this report, that most of the findings of this study presumably do not apply to them, although the growth trends of the North Atlantic area, of Latin America, and of the countries of Southeast Asia obviously have an important bearing on the growth of economic activity in all other regions. The data on which much of the discussion is based are summarized in Tables i and 2 below.